2021
DOI: 10.3390/biom11081197
|View full text |Cite
|
Sign up to set email alerts
|

Integrin β4 as a Potential Diagnostic and Therapeutic Tumor Marker

Abstract: Integrin β4 (ITGβ4) is a class of transmembrane adhesion molecules composed of hemidesmosomes (HDs). Its unique long intracellular domain provides intricate signal transduction functions. These signal transduction effects are especially prominent in tumors. Many recent studies have shown that integrin β4 is differentially expressed in various tumors, and it plays a vital role in tumor invasion, proliferation, epithelial–mesenchymal transition, and angiogenesis. Therefore, we categorize the research related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…Research on glioblastoma and breast cancer supports the suggested pancancer involvement of integrin α6 in radioresistance [65] , [66] . Concerning integrin β4, a connection to EMT could be observed [67] , which was also identified as a hallmark ontology in our final aaGOI-All/RT set. Likewise, both of these integrins and their heterodimeric α6β4 receptors were found to be intricately involved in cancer stem cell (CSC) properties [46] and their deactivation demonstrated effective perturbation of CSC populations [68] , [69] .…”
Section: Discussionmentioning
confidence: 90%
“…Research on glioblastoma and breast cancer supports the suggested pancancer involvement of integrin α6 in radioresistance [65] , [66] . Concerning integrin β4, a connection to EMT could be observed [67] , which was also identified as a hallmark ontology in our final aaGOI-All/RT set. Likewise, both of these integrins and their heterodimeric α6β4 receptors were found to be intricately involved in cancer stem cell (CSC) properties [46] and their deactivation demonstrated effective perturbation of CSC populations [68] , [69] .…”
Section: Discussionmentioning
confidence: 90%
“…There is ample evidence that the most important functional states of cells (stemness, EMT, invasion, migration, proliferation, and tumor angiogenesis) are associated with α6β4 integrin expression ( Romagnoli et al, 2019 ; Bierie et al, 2017 ; Masugi et al, 2015 ; Yang et al, 2021 ; Roussellea & Scoazecb, 2020 ). It is also known that α6β4 expression is associated with a poor prognosis in breast cancer patients ( Lu et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 29 ITGB4 is a signaling protein that promotes intracellular signaling and protects the integrity of epithelial cells. 30 Moreover, bioinformatics analysis showed that ITGB4 acts as a pan-cancer oncogene in 33 different types of human tumors. 31 ITGB4 overexpression has been associated with venous invasion and decreased overall survival in patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%